2005
DOI: 10.1002/ajim.20235
|View full text |Cite
|
Sign up to set email alerts
|

Developing search strategies in Medline on the occupational origin of diseases

Abstract: To search for studies on the occupational origin of diseases in Medline, we propose to start with the proper name for the occupational disease. If this does not exist, use a specific term for the occupation and type of industry in combination with terms for disease. To improve the sensitivity of the search, a search term for the specific risk factor should be added. If there is no relevant occupational title available, it is worth trying the general search terms occupational diseases or occupational risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 20 publications
0
31
0
1
Order By: Relevance
“…A number of projects was dealing with search strategies and is published already [12][13][14][15] . One project evaluated AGREE (Appraisal of Guidelines for REsearch and Evaluation) as a quality assessment system for practice guidelines 16) .…”
Section: The Dutch Knowledge Infra Structure (Kis) Programmementioning
confidence: 99%
See 1 more Smart Citation
“…A number of projects was dealing with search strategies and is published already [12][13][14][15] . One project evaluated AGREE (Appraisal of Guidelines for REsearch and Evaluation) as a quality assessment system for practice guidelines 16) .…”
Section: The Dutch Knowledge Infra Structure (Kis) Programmementioning
confidence: 99%
“…Concrete health care activities such as a diagnostic medical examination might be wanted by a worker, or a workers' council might like to discuss with experts the need for a screening programme. Then OH professionals are needed with practical experience and Industrial Health 2007, 45, [13][14][15][16][17][18] able to transfer and interpret scientific knowledge.…”
mentioning
confidence: 99%
“…Preliminary samples of abstracts were collected for all terms identified on the basis of findings from a single available study on PubMed searches regarding occupational etiology [Schaafsma et al, 2006], analysis of MeSH entry terms, the authors' experience and brainstorming. After extensive evaluation (data not shown), 61 terms were included in our study as free-search (see Table I).…”
Section: Selection Of Terms To Be Testedmentioning
confidence: 99%
“…In the Occupational Medicine field, search strategies have been proposed for the retrieval of intervention studies or etiological research papers [Verbeek et al, 2005;Haafkens et al, 2006;Schaafsma et al, 2006;Mattioli et al, 2010]. In addition, a controlled trial showed that evidence-based search strategies may enhance the effectiveness of the consultation of PubMed [Schaafsma et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, optimized search strategies have to be adopted to maximize the impact of searching in terms of quality and time [9][10][11][12][13][14][15]. We recently formulated the first search strings in endocrinology to investigate pituitary disorders [16].…”
Section: Introductionmentioning
confidence: 99%